Oleasylva: meeting on oil seed trees and their uses - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1992)
gathering of 30 experts on oil seed trees in the Sahelian regions. The meeting, called Oleasylva, was held in Bamako Mali in July 1992.